Chemical and thermal stability studies of hydrophobic and hydrophilic Polyvinylidene Fluoride (PVDF) membranes in alkaline environments / Mohamad Fairus Rabuni - Mohamad Fairus, Rabuni (2014)
This research work has highlighted the effects of alkaline solution towards PVDF stability at the typical concentrations used in membrane cleaning and membrane contactor processes such as gas absorption using alkaline solution. In the first part of the study, PVDF membranes treated with two types of strong alkali, sodium hydroxide (NaOH) and potassium hydroxide (KOH) at different concentrations, temperatures and treatment times. The virgin and treated membranes were analysed using FESEM, DSC, FTIR, pure water flux measurement and tensile test. PVDF membrane was found to experience changes in its intrinsic properties following exposure towards alkaline solution. For 120 minute treatment at 50 °C, the nominal elongation values decreased to 75% and 73% for membrane immersed in 0.2 M KOH and NaOH, respectively. The results demonstrated that PVDF membrane can be attacked and degraded upon exposure, even to a low concentration of 0.01 M alkaline solution, the concentration that is commonly applied in membrane contactor applications and cleaning. The findings from this study also suggested that PVDF membrane is more vulnerable to NaOH solution as compared to KOH solution. In membrane cleaning study, all cleaning conditions failed to achieve complete flux restoration except for the membrane cleaned at the extreme condition (concentrated chemical, high temperature and longest cleaning period) with cleaning efficiency (Ce) was measured to be more than 1. Increased water flux over the virgin membrane value signifies the alteration in membrane properties subsequent to a cleaning process. Overall, NaOCl was observed to be more efficient in removing protein (BSA) particles than NaOH; however, it causes a further decline in membrane stability. The efficiency of protein filtration was compromised during the use of cleaned membrane where it gave lower protein retention. This phenomenon is mainly linked to membrane hydrophilicity and pore structure in which the cleaned membrane results in a poor performance for protein rejection.